Surface porous catalytic material based on rose-stripe Damascus steel as well as preparation method and application of surface porous catalytic material

By forming a two-region three-dimensional block porous structure on the surface of rose-shaped Damascus steel, the problem of difficult to balance the catalytic activity and selectivity of existing porous metal catalytic materials when treating dye wastewater is solved, and the effect of efficient degradation of dye wastewater is achieved.

CN119237026APending Publication Date: 2025-01-03NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411359054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When existing porous metal catalytic materials treat dye wastewater, their catalytic activity and selectivity are difficult to balance, and they are easily crushed by dye solution, which has low degradation efficiency and cannot effectively degrade complex dye wastewater.

Method used

Rose-patterned Damascus steel is used as the matrix, and a two-region three-dimensional block porous structure is obtained through dealloyment treatment, forming alternatingly distributed irregular pores and ligaments, improving catalytic activity and mechanical properties, and enhancing the degradation ability of dyes.

Benefits of technology

It has achieved efficient degradation of dye wastewater, with a degradation efficiency of 94%, and the material itself maintains integrity, ensuring long-term use and efficient degradation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237026A_ABST
    Figure CN119237026A_ABST
Patent Text Reader

Abstract

The invention provides a surface porous catalytic material based on rose-stripe damascene steel, the catalytic material takes the rose-stripe damascene steel as a matrix, the matrix comprises a first area and a second area, and the first area and the second area are both in a closed ring shape and are alternately distributed to form rose stripes; wherein irregular pore channels are uniformly distributed on the surfaces of the first area and the second area, and the average width of the pore channels is smaller than that of the ligament, so that a three-dimensional blocky porous structure is formed; the hole channels and the ligaments in the first area are defined as first hole channels and first ligaments correspondingly, and the hole channels and the ligaments in the second area are defined as second hole channels and second ligaments correspondingly; the average width of the first pore channels is larger than that of the second pore channels, the average depth of the first pore channels is larger than that of the second pore channels, and the average width of the first ligament is smaller than that of the second ligament. The double-region three-dimensional blocky porous structure of the material disclosed by the invention has high catalytic activity, and dye molecules can be degraded more effectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous metal catalytic materials, and in particular to a surface porous catalytic material based on rose-grained Damascus steel, and a preparation method and application thereof. Background Art

[0002] Dye wastewater is one of the most difficult industrial wastewaters and environmental toxins to treat. Its discharge will cause serious pollution to water bodies and soil. Most of the dyes are highly toxic, dark in color, high in organic matter content, and difficult to degrade. When they are discharged into water bodies, they will cause serious pollution to the environment and endanger human health. Traditional treatment methods, such as physical adsorption, microbial degradation, and chemical oxidants, are complex, time-consuming, and labor-intensive to treat these dye wastewaters. They cannot be completely degraded and will also cause secondary pollution to the water body.

[0003] Porous metal catalytic materials, because of their large number of pore structures on the surface, can provide a large specific surface area, thereby significantly enhancing the contact between the catalyst and the reactants and improving the activity of the catalyst. Porous metal catalytic materials have attracted widespread attention due to their excellent performance in catalytic reactions.

[0004] Iron-based single-stage porous materials are typical porous metal catalytic materials, which have a three-dimensional bicontinuous nanopore metal structure. The catalytic activity can be improved by the continuous nanopore structure. However, due to the single pore size, it is impossible to achieve a balance between the activity of the catalyst and the selectivity for the target product. For complex wastewater systems such as dye wastewater, the catalytic effect is not satisfactory.

[0005] The iron-based two-stage porous structure establishes secondary pores on the ligaments of the single-stage porous structure. Through the two-stage pores, the specific surface area is further increased, the catalytic efficiency is improved, and to a certain extent, the activity of the catalyst and the selectivity for the target product are balanced. However, generally, the pore sizes of this two-stage porous structure are too different. Due to the influence of the surface tension of the catalytic medium, the secondary porous structure cannot effectively degrade the dye solution, which ultimately limits the improvement of the degradation efficiency in the entire catalytic process.

[0006] Moreover, in the prior art, such porous metal catalytic materials are mostly in the form of strips, and surface stress will produce stress concentration phenomenon, which can be easily broken by the dye solution in actual application, resulting in reduced degradation efficiency or even inability to further degrade. Summary of the invention

[0007] The purpose of the present invention is to provide a surface porous catalytic material based on rose Damascus steel and a preparation method thereof in view of the deficiencies in the prior art. Rose Damascus steel is used as a substrate, and a dual-region three-dimensional block porous structure is obtained by dealloying, so as to improve the catalytic activity and more effectively degrade dye molecules.

[0008] According to a first aspect of the present invention, a surface porous catalytic material based on rose-patterned Damascus steel is provided. The catalytic material uses rose-patterned Damascus steel as a matrix, and the matrix includes a first region and a second region. The first region and the second region are both closed rings, and the first region and the second region are alternately distributed to form a rose pattern.

[0009] Wherein, irregular channels are distributed on the surfaces of the first region and the second region, and the average width of the channels is smaller than the average width of the ligaments, thereby forming a three-dimensional block-shaped porous structure;

[0010] The pores and ligaments in the first region are defined as first pores and first ligaments, respectively, and the pores and ligaments in the second region are defined as second pores and second ligaments, respectively;

[0011] The average width of the first channel is greater than the average width of the second channel, the average depth of the first channel is greater than the average depth of the second channel, and the average width of the first ligament is less than the average width of the second ligament.

[0012] As an optional embodiment, the average width of the first channel is 430nm to 1220nm, and the average width of the second channel is 240nm to 740nm.

[0013] As an optional embodiment, the average width of the first ligament is 0.05 μm to 0.43 μm, and the average width of the second ligament is 0.75 μm to 1.93 μm.

[0014] As an optional embodiment, nanowire structures are diffusely distributed on the surface of the first ligament.

[0015] As an optional embodiment, the composition of the first region, by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe;

[0016] The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

[0017] As an optional implementation, the thickness of the substrate is 1 mm to 20 mm.

[0018] According to a second aspect of the present invention, there is provided a method for preparing the aforementioned surface porous catalytic material based on rose-grained Damascus steel, comprising:

[0019] The pretreated rose-grain Damascus steel is placed in an acid solution for dealloying, and after the dealloying is completed, it is washed with deionized water until it is neutral, and dried at room temperature to obtain a surface porous catalytic material;

[0020] The rose-patterned Damascus steel has a first area and a second area that are alternately distributed, and both the first area and the second area are closed ring-shaped;

[0021] The composition of the first region, by mass fraction, includes: C: 0.16% to 0.25%, Mn ≤ 1.00%, Si ≤ 1.00%, Cr: 12.00% to 14.00%, Ni ≤ 0.75%, P ≤ 0.04%, S ≤ 0.03%, and the rest is Fe;

[0022] The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

[0023] As an optional implementation, hydrochloric acid with a pH value less than 7 is used for dealloying, and the dealloying time is 48 hours to 168 hours.

[0024] According to a third aspect of the present invention, there is provided a multi-stage pipeline continuous degradation reaction device, comprising a plurality of interconnected pipelines, each stage of the pipeline is provided with a controller for controlling the rotation of the rotor blades, and a water inlet is provided on the first stage of the pipeline, and a water outlet is provided on the last stage of the pipeline;

[0025] Among them, each stage of the pipeline is equipped with multiple sets of series-connected rotor blades, and the material of the rotor blades is the aforementioned surface porous catalytic material based on rose-patterned Damascus steel.

[0026] According to a fourth aspect of the present invention, there is provided a degradation method for treating dye wastewater using the aforementioned multi-stage pipeline continuous degradation reaction device.

[0027] It can be seen from the above technical solutions of the present invention that the surface porous catalytic material based on rose-grained Damascus steel proposed by the present invention has a dual-region three-dimensional block porous structure, the two regions have two-level pores respectively, and the width of the ligament region is relatively large;

[0028] On the one hand, the wider ligaments allow the pollutant liquid to flow quickly, providing diffusion and transmission channels for the reaction molecules, providing more attachment points for the degradation reaction, and accelerating the reaction speed;

[0029] On the other hand, in the two-level pores, the larger pores increase the mass transfer efficiency of the catalyst, allowing the reactant molecules to diffuse into the interior of the catalyst faster, contact with the active sites and react; the reactant molecules diffuse faster through the large pores to the small pore area adjacent to it, and the ligaments in the small pore area have a nanowire structure, which further accelerates the diffusion of the reactant molecules. At the same time, the smaller pores accommodate more active components and improve the catalytic efficiency. At the same time, the small pores are deeper, and the pollutant liquid prolongs the contact time with the target pollutant during the slow infiltration process, and the two alternating distribution areas enable the catalyst to more effectively capture almost all pollutants.

[0030] Thus, the surface porous catalytic material based on rose-grained Damascus steel of the present invention can efficiently degrade dye wastewater, with a degradation efficiency of up to 94%, and can degrade almost all polluting molecules.

[0031] The surface porous catalytic material of the present invention has a certain thickness and is porous treated on the surface, has excellent mechanical properties, and can ensure the integrity of the material itself during the entire treatment process, thereby ensuring smooth degradation and having high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a picture of an exemplary rose-patterned Damascus steel matrix.

[0033] Figure 2 It is a structural schematic diagram of a multi-stage pipeline continuous degradation reaction device in an example of the present invention.

[0034] Figure 3 is a morphology diagram of the material of Example 1 of the present invention; wherein 3a is a macroscopic metallographic diagram of the rose-grained Damascus steel matrix before treatment; 3b is a macroscopic SEM diagram of the material after treatment Figure 3 c is a 2000x SEM image of area A after treatment; 3d is a 20000x SEM image of area A after treatment; 3e is a 2000x SEM image of area B after treatment; 3f is a 20000x SEM image of area B after treatment.

[0035] Figure 4 It is the ultraviolet spectrum of the material of Example 1 of the present invention that degrades methyl into dye. DETAILED DESCRIPTION

[0036] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0037] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0038] Rose Damascus steel is formed by combining two or more materials with different properties through carburizing, repeated folding, and forging. By controlling different folding methods and forging techniques, different microstructure patterns with certain periodic cyclic characteristic structures are presented. Figure 1 As shown. Damascus steel has the advantages of high strength, hardness and good toughness.

[0039] Based on this, the present invention adopts rose-patterned Damascus steel as the matrix material, and adopts a dealloying method to obtain a dual-region three-dimensional lamellar porous structure on the matrix.

[0040] Surface porous catalytic materials based on rose-grained Damascus steel

[0041] In an exemplary embodiment of the present invention, a surface porous catalytic material based on rose-patterned Damascus steel is provided. The catalytic material uses rose-patterned Damascus steel as a matrix, and the matrix includes a first region and a second region. The first region and the second region are both closed rings, and the first region and the second region are alternately distributed to form a rose pattern.

[0042] Irregular pores are distributed on the surfaces of the first region and the second region, and the average width of the pores is smaller than the average width of the ligaments, thereby forming a three-dimensional block-shaped porous structure.

[0043] The pores and ligaments in the first region are defined as first pores and first ligaments, respectively, and the pores and ligaments in the second region are defined as second pores and second ligaments, respectively;

[0044] The average width of the first channel is greater than the average width of the second channel, the average depth of the first channel is greater than the average depth of the second channel, and the average width of the first ligament is less than the average width of the second ligament.

[0045] It can be understood that the blocky in the three-dimensional blocky porous structure of the present invention means that the average width of the pores is smaller than the average width of the ligaments. From the microstructure diagram, the pores are similar to cracks, which divide the matrix into blocks, and therefore it is defined as a three-dimensional blocky porous structure.

[0046] As an optional example, the average width of the first channel is 430 nm to 1220 nm, and the average width of the second channel is 240 nm to 740 nm.

[0047] As an optional example, the average width of the first ligament is 0.05 μm to 0.43 μm, and the average width of the second ligament is 0.75 μm to 1.93 μm.

[0048] As an optional example, the surface of the first ligament is diffusely distributed with nanowire structures, which can further accelerate the diffusion of reactant molecules.

[0049] As an optional example, the composition of the first region, by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe;

[0050] The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

[0051] In a specific example, the first region is 20Cr13 and the second region is 06Cr18Ni9Cu2.

[0052] As an optional embodiment, the thickness of the substrate is 1 mm to 20 mm. The thicker substrate ensures that the porous material has excellent mechanical properties and can ensure the integrity of the material itself during the entire processing process, thereby ensuring smooth degradation and high degradation efficiency.

[0053] It can be understood that the thickness of the substrate includes but is not limited to the above range of values, and can be selected as needed. The substrate can even have a non-uniform thickness as needed.

[0054] Preparation method of surface porous catalytic material based on rose-grained Damascus steel

[0055] In another exemplary embodiment of the present invention, a method for preparing the aforementioned surface porous catalytic material based on rose-grained Damascus steel is provided, comprising:

[0056] The pretreated rose-grain Damascus steel is placed in an acid solution for dealloying. After the dealloying is completed, it is washed with deionized water to neutrality and dried at room temperature to obtain a surface porous catalytic material.

[0057] The rose-patterned Damascus steel has a first area and a second area that are alternately distributed, and both the first area and the second area are closed rings;

[0058] The composition of the first region, by mass fraction, includes: C: 0.16% to 0.25%, Mn ≤ 1.00%, Si ≤ 1.00%, Cr: 12.00% to 14.00%, Ni ≤ 0.75%, P ≤ 0.04%, S ≤ 0.03%, and the rest is Fe;

[0059] The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

[0060] In the aforementioned component system, the second region has relatively higher Cr and Ni contents than the first region, and the second region has more Cu elements than the first region. When the rose-grained Damascus steel is in HCl, the first region adjacent to the second region has a more negative electrode potential than the second region, and micro-galvanic corrosion occurs. The first region acting as the anode corrodes more severely than the second region acting as the cathode, thus forming two different three-dimensional blocky porous structures.

[0061] In a specific example, the wavy Damascus steel used as the substrate can be purchased directly. The pretreatment process generally involves removing surface impurities and oil stains, then removing the surface oxide layer, polishing to remove grinding scratches, and then drying for use.

[0062] As an optional example, hydrochloric acid with a pH value less than 7 is used for dealloying, and the dealloying time is 48 hours to 168 hours.

[0063] Application of surface porous catalytic materials based on rose-grained Damascus steel

[0064] like Figure 2 As shown, in another exemplary embodiment of the present invention, a multi-stage pipeline continuous degradation reaction device is provided, comprising a plurality of interconnected pipelines 10.

[0065] Therein, a plurality of sets of rotating blades 11 connected in series are arranged in the pipeline 10, and the material of the rotating blades 11 is the aforementioned surface porous catalytic material based on rose-grained Damascus steel.

[0066] As an example, the rose-patterned Damascus steel base material can be directly forged into a rotor blade shape, and then processed using the aforementioned method to obtain a dual-region three-dimensional block-like porous structure on the base, which can be directly used as a rotor blade of a multi-stage pipeline continuous degradation reaction device.

[0067] Each stage of the pipeline is equipped with a controller 12 for controlling the rotation of the impeller, and a water inlet 13 is provided on the first stage of the pipeline, and a water outlet 14 is provided on the last stage of the pipeline.

[0068] When treating sewage, the rotor blades 11 in each level of the pipeline are first started, and then the sewage to be degraded enters the first-level pipeline through the water inlet 13, flows into the second-level pipeline for rotor blade catalytic treatment after being catalytically treated by the rotor blades 11, and then enters the third pipeline for catalytic treatment in turn, until it flows out from the water outlet 14 after being treated in the last level of the pipeline, thus completing the entire treatment process.

[0069] As an optional example, the diameter of the pipeline 10 can be set to decrease step by step from the first stage to the last stage, so that the size of the impellers in the corresponding pipeline also decreases step by step, but the wastewater flow rate will increase, thereby improving the reaction efficiency and accelerating the degradation rate, while reducing costs and being more suitable for industrial applications.

[0070] It is understandable that during the entire degradation process, the reaction conditions can be adjusted according to actual conditions, or subsequent treatment can be performed; for example, electrochemical treatment can be combined in a multi-stage pipeline continuous degradation reaction device.

[0071] In the embodiments of the present invention, in view of the demand for rapid degradation treatment of dye wastewater, combined with the design of the aforementioned multi-stage pipeline continuous degradation reaction device, a rotary vane (i.e., a rotary blade) is configured as a degradation catalytic material, which can be driven to rotate. During the rotation process, the rapid degradation process of the dye wastewater is accelerated and promoted. The catalytic efficiency is increased by more than 50% relative to the static catalytic material. However, higher requirements are placed on the strength and wear resistance of the rotary vane as the catalytic material. The surface porous catalytic material of the rose Damascus steel proposed by the present invention, on the one hand, uses the rose Damascus steel as a substrate, which has the advantages of high strength, high hardness and good toughness. On the other hand, through the dealloying process on its surface The formed surface porous catalytic structure, that is, two three-dimensional block porous structures of different sizes formed in alternating areas on the surface of rose-patterned Damascus steel, combined with the rotating action of the rotary blades, allows the polluted wastewater to quickly pass through the three-dimensional block porous structure of the alternating first area and second area, which not only improves the rapid diffusion speed and efficiency of the polluted wastewater, but also provides more catalytic sites, and the deeper pores extend the contact time between the pollutants and the catalytic material, so that the pollutant molecules in the wastewater are fully combined and catalyzed by the active sites, thereby improving the degradation efficiency. Through the alternating degradation effect, the catalytic decomposition efficiency and effect of the pollutant molecules are further guaranteed. The catalytic effect of 4 hours reaches more than 94%, achieving the purpose of efficient decomposition and catalysis.

[0072] At the same time, through the catalytic decomposition test, in the rotor blade structure of the embodiment of the present invention, after 4 hours of continuous rotation and catalytic decomposition, the rotor blade structure and the surface porous catalytic material layer remained intact and the morphology was basically unchanged, ensuring the long-term service life and degradation effect.

[0073] As an example, in one of the embodiments, a degradation method for treating dye wastewater using the aforementioned multi-stage pipeline continuous degradation reaction device is provided, comprising: in each stage of the multi-stage pipeline continuous degradation reaction device, or in any stage of the pipeline, using the aforementioned surface porous catalytic material based on rose-grained Damascus steel as a working electrode, Pt as a counter electrode, and Ag / AgCl saturated electrode as a reference electrode in a three-electrode electrochemical system, using dye wastewater as an electrolyte, and using a cyclic square wave mode to degrade the dye wastewater at 40°C.

[0074] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0075] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0076] The rose-grained Damascus steel used in the embodiment is made of two steels with different compositions, wherein the A region is 06Cr18Ni9Cu2 and the rest is Fe, and its composition (mass fraction, wt%) is as follows:

[0077]

[0078] The B area is 20Cr13, and the rest is Fe. Its composition (mass fraction, wt%) is as follows:

[0079] element C Mn Si Cr Ni P S Content / wt% 0.16-0.25 ≤1.00 ≤1.00 12.00-14.00 ≤0.75 ≤0.04 ≤0.03

[0080] Example 1

[0081] Use alcohol solution to remove impurities and oil stains on the surface of 12×10×3mm rose-patterned Damascus steel, and then polish it one by one with sandpaper of roughness 80, 240, 400, 600, 800, 1000, 1200, 1500, 2000, and 3000. When using 80# sandpaper for polishing, make sure to remove the oxide layer on the surface of the sample.

[0082] After the rose-patterned Damascus steel is polished, it is polished on a polishing machine with the help of a polishing cloth and silica polishing liquid. After the scratches during polishing are eliminated, anhydrous ethanol is used for ultrasonic treatment for 10 minutes to remove impurities on the surface.

[0083] The pretreated rose-grain Damascus steel was placed in a 0.1 mol / L hydrochloric acid solution for surface pickling for 168 hours to obtain a surface porous catalytic material.

[0084] Example 2

[0085] [SEM]

[0086] The surface porous catalytic material of Example 1 was subjected to SEM test. The results are as follows: Figure 3 shown.

[0087] Figure 3 a is a macroscopic image of the matrix material, where rose patterns can be seen, with the light-colored area being marked as area A and the dark-colored area being marked as area B.

[0088] Figure 3 b is the macroscopic SEM image of the material after matrix treatment. It can be seen from the figure that the rosette pattern is not destroyed, and the material still has two regions A and B, which are distributed alternately with each other.

[0089] Figure 3 c and 3d, Figure 3 e and 3f are high-magnification images of region A and region B in 3b, respectively. It can be seen from the figure that the pores in region B ( Figure 3 e) than the pores in area A ( Figure 3 c) Wider, the pores in area A ( Figure 3 d) The depth of the hole is not as deep as that of area B ( Figure 3 f) and combined Figure 3 f It can be seen that the nanostructures are diffusely distributed on the ligament surface in area B.

[0090] According to the statistics of SEM images, the average width of the pores in region A is 240nm-740nm, and the average width of the ligaments in region A is 0.75μm-1.93μm; the average width of the pores in region B is 430nm-1220nm, and the average width of the ligaments in region B is 0.05μm-0.43μm.

[0091] It can be seen from the above that the present invention successfully prepared a surface porous catalytic material based on rose-patterned Damascus steel.

[0092] Example 3

[0093] [Catalytic performance]

[0094] Test sample (Porous 40°C): simulated wastewater, i.e., methyl orange solution with a concentration of 20 mg / L, was used as the degradable wastewater, and a multi-stage pipeline continuous degradation reaction device was used for degradation (in this test, there were three pipelines, and each pipeline was equipped with multiple sets of rotor blades, and the rotor blades were materials obtained by the method of Example 1). Then, in the first pipeline, the surface porous catalytic material obtained in Example 1 was used as the working electrode, Pt was used as the counter electrode, and Ag / AgCl (saturated) electrode was used as the reference electrode to form a three-electrode electrochemical system, and 50 mL of 20 mg / L methyl orange solution was used as the electrolyte. The electrolyte was treated in a water bath at 40°C using a cyclic square wave mode (the upper potential of the square wave was +1.5 V, the lower potential was -1.5 V, the holding time was 60 s, and the number of cycles was 120 times). After 240 minutes, a sample was taken from the water outlet, the solid and liquid were separated by a centrifuge, and the supernatant was taken, and the light absorption performance of the sample was tested by an ultraviolet spectrophotometer.

[0095] After the degradation was completed, after 4 hours of continuous rotation catalytic decomposition, the structure of the Damascus steel body as the matrix and the structure and morphology of the porous catalytic material on the surface of the test sample remained basically unchanged, maintaining a high degree of integrity.

[0096] Comparative sample 1 (Original 25°C) is different from the test sample in that rose-grained Damascus steel (pretreatment completed) without dealloying is used as the working electrode, and degradation is carried out at 25°C.

[0097] Comparative sample 2 (Porous 25°C) is treated differently from the test sample in that the degradation is carried out at 25°C.

[0098] from Figure 4 It can be seen that by examining the absorbance at 465 nm, the degradation rate is calculated according to formula (1):

[0099] Degradation rate

[0100] Where A0 is the initial absorbance value of methyl orange, and A is the absorbance value of methyl orange after degradation.

[0101] According to the above formula, it is calculated that the degradation efficiency of the test sample is 94.15%, the degradation rate of the comparative sample 1 is 34.28%, and the degradation rate of the comparative sample 2 is 45.03%.

[0102] It can be seen that by using the catalytic material of the present invention to degrade the methyl orange solution, the methyl orange molecules can be efficiently degraded.

[0103] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A surface porous catalytic material based on rose-grained Damascus steel, characterized in that: The catalytic material uses rose-patterned Damascus steel as a matrix, the matrix comprising a first region and a second region, the first region and the second region are both closed rings, and the first region and the second region are alternately distributed to form a rose pattern; Wherein, irregular channels are distributed on the surfaces of the first region and the second region, and the average width of the channels is smaller than the average width of the ligaments, thereby forming a three-dimensional block-shaped porous structure; The pores and ligaments in the first region are defined as first pores and first ligaments, respectively, and the pores and ligaments in the second region are defined as second pores and second ligaments, respectively; The average width of the first channel is greater than the average width of the second channel, the average depth of the first channel is greater than the average depth of the second channel, and the average width of the first ligament is less than the average width of the second ligament.

2. The surface porous catalytic material based on rose-grained Damascus steel according to claim 1, characterized in that: The average width of the first channel is 430nm-1220nm, and the average width of the second channel is 240nm-740nm.

3. The surface porous catalytic material based on rose-grained Damascus steel according to claim 1, characterized in that: The average width of the first ligament is 0.05 μm to 0.43 μm, and the average width of the second ligament is 0.75 μm to 1.93 μm.

4. The surface porous catalytic material based on rose-grained Damascus steel according to claim 1, characterized in that: Nanowire structures are diffusely distributed on the surface of the first ligament.

5. The surface porous catalytic material based on rose-grained Damascus steel according to claim 1, characterized in that: The composition of the first region, calculated by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe; The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

6. The surface porous catalytic material based on rose-grained Damascus steel according to claim 1, characterized in that: The thickness of the substrate is 1 mm to 20 mm.

7. A method for preparing a surface porous catalytic material based on rose-grained Damascus steel according to any one of claims 1 to 6, characterized in that: include: The pretreated rose-grain Damascus steel is placed in an acid solution for dealloying, and after the dealloying is completed, it is washed with deionized water until it is neutral, and dried at room temperature to obtain a surface porous catalytic material; The rose-patterned Damascus steel has a first area and a second area that are alternately distributed, and both the first area and the second area are closed ring-shaped; The composition of the first region, calculated by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe; The components of the second region, calculated by mass fraction, include: C≤0.08%, Si≤1.00%, Mn≤2.00%, P≤0.045%, S≤0.030%, Ni: 8.00%~10.50%, Cr: 17.00%~19.00%, Cu: 1.00%~3.00%, and the rest is Fe.

8. The preparation method according to claim 7, characterized in that: The dealloying treatment is carried out using hydrochloric acid with a pH value less than 7, and the dealloying time is 48 hours to 168 hours.

9. A multi-stage pipeline continuous degradation reaction device, characterized in that: It comprises a plurality of interconnected pipes (10), each stage of the pipes is provided with a controller (12) for controlling the rotation of the impellers, and a water inlet (13) is provided on the first stage of the pipe, and a water outlet (14) is provided on the last stage of the pipe; Wherein, a plurality of sets of rotating blades (11) connected in series are arranged in each stage of the pipeline, and the material of the rotating blades (11) is the surface porous catalytic material based on rose-grained Damascus steel as described in any one of claims 1 to 6.

10. A degradation method for treating dye wastewater using the multi-stage pipeline continuous degradation reaction device according to claim 9.